Efektivitas Penggunaan Media Digital Google Form dalam Evaluasi Belajar Siswa - Fitriani, Fitriani; Jamin, Hanifuddin; Abidah, Abidah (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2024)
In this digital era, the student evaluation process can be carried out anywhere and at any time, this makes teachers think creatively about using information and communication technology in student evaluation activities. One method used by teachers in the student evaluation process is by using the Google Form application. This research is about